Terjemah sunan an Nasa'iy - Abu Abdur Rahman Ahmad An Nasa'iy (C.V. Asy Syifa, 1992)
OenJil. I=C.1-6;Jil.II=C.1-6;Jil.III=c.1-4 Jil.IV=c.1, /tr, jil.1=c.7; jil.3=c.5; jil.4=c.2/tr, jil.1=c.8-9; jil.2=c.8/ir, jil.3, c.6-7/jil.1=c.10-11